Experimental Study of the Shear Behavior of Self Compacted Concrete T-Beams - Sh. Mahmoud, Kamal (Journal of Engineering and Sustainable Development, 2012)
Twelve self compacted concrete (SCC) T-section beams were design and tested to determine the effect of using SCC on the shear behavior under two concentrated loads. All beams have the same longitudinal steel ratio of (0.018823) and gross section area of (20000) mm2. The tested beams were divided into two groups- with and without stirrups. The first group consists of three beams without stirrup and with different values of compressive strength (f’c).While the second group consists of nine beams with stirrups. It were divided into three series according to the compressive strength (f’c ) each series have three beams with different value of clear span to effective depth ratio (ln/d). It was found that The ultimate shear strength predicated from ACI 318M-08 is conservative prediction than the experimental values, The clear span to the effective depth ratio (ln/d) has a significant influences on the ultimate shear strength, The ultimate shear strength of SCC T-beams with stirrups increased about 28.57%.10.714%and 10.169%; when the compressive strength (f’c ) increased from (29.36 to 49.2 MPa), the ultimate shear strength of SCC T-beams without stirrups increased about 55.55%; when the compressive strength (f’c ) increased from (29.36 to 49.2 MPa).